Cardiovascular risk factors with an emphasis on hypertension in the Mura Indians from Amazonia - Zilmar Augusto de Souza Filho (BMC Public Health, 2018)
Abstract Background The Brazilian indigenous population is currently undergoing a process of epidemiological transition regarding the occurrence of communicable diseases, malnutrition and non-communicable chronic diseases. Chronic non-infectious diseases are the most common causes of death worldwide, and hypertension is one of the main cardiovascular risk factors. Thus, the main objective of this paper was to evaluate the prevalence of cardiovascular risk factors, with an emphasis on hypertension, in the Mura Indians living in the municipality of Autazes in the northern Brazilian state of Amazonas. Methods This cross-sectional study was conducted among 455 natives (57.8% women, 42.2 ± 16.7 years) selected by simple random sampling. Sociodemographic variables, habits and lifestyles, anthropometric data, fasting glycaemia and lipid profiles were evaluated. Blood pressure was measured with a validated automatic device. Values of p ≤ 0.05 were considered significant. Results The prevalence of hypertension was 26.6%. The other cardiovascular risk factors were as follows: increased waist-hip ratio (85.1%); increased neck circumference (60.2%); increased waist circumference (48.6%); overweight (57.1%); physical inactivity (52.7%); use of alcoholic beverages (40.2%); high total cholesterol (27.5%); increased triglycerides (23.5%); smoking (20.4%); and diabetes mellitus (3.0%). In relation to non-hypertensive individuals, indigenous hypertensive individuals were (p ≤ 0.05) older and had a higher proportion of individuals living with partners and individuals who were retired, as well as a lower level of schooling and higher family income. The indigenous people living in urban areas had a higher prevalence of hypertension than did those living in rural areas. In relation to habits and lifestyles, hypertensive Indians had a lower prevalence of smoking, higher frequency of the use of animal fat during meal preparation, lower frequency of vegetable oil use and lower frequency of salt addition to already-prepared meals. An assessment of anthropometric variables and laboratory markers showed that the hypertensive indigenous individuals had higher values of body mass index, neck circumference, waist circumference, visceral fat, Conicity Index, and body fat than did the non-hypertensive individuals. Conclusion The prevalence of hypertension and other important cardiovascular risk factors in the Mura Indians was high. This finding is probably due to the adoption of inappropriate habits and lifestyles.